Evaluating GPS CORS Data for Crustal Deformation Analysis in East Java - Irene Rwabudandi; Ira Mutiara Anjasmara; Susilo Susilo (Jurnal Teknik ITS, 2019)
The tectonic setting of Indonesia is very complex due to its location on the boundaries of several major tectonic plates. The complexity of the tectonics also makes Indonesia prone to natural disasters such as earthquakes, tsunamis, volcanic eruptions etc. Crustal deformation caused by the tectonics activities can be monitored using geodetic techniques such as Global Positioning System (GPS) survey, Interferometry Synthetic Aperture Radar (InSAR) processing, etc. In this research, we analyze the crustal deformation in the northern part of East Java using ten GPS Continuously Operating Reference Stations (CORS) data provided by the Indonesian Geospatial Information Agency from 2015 to 2018. The results showed the horizontal movement toward southeast for all the stations. The horizontal velocity rates are range between 2.63 cm/yr and 2.96 cm/yr. For the vertical displacements, nine stations are subject to subsidence with the rates range from -0.021cm/yr to -0.4 cm/yr that we suspect related to the geological settings of the study area.